Environmental drivers of taxonomic and phylogenetic diversity patterns of plant communities in semi-arid steppe rangelands of North Africa - Amale Macheroum (Elsevier, 2021)
Since phytoecological and biodiversity studies deepen our understanding on ecosystem functioning and habitat health status of rangelands, this study analyzed the composition and plant taxonomic and phylogenetic diversity of semi-arid steppe vegetation communities in rangelands of northeastern Algeria. Based on 80 floristic samples, vegetation was analyzed using various species diversity parameters (incidence- and abundance-based diversity and similarity indices, rarefaction and extrapolation estimations). Sampling totaled 75,197 plant individuals that were classified into 63 species, 55 genera and 21 families, with predominance of Asteraceae (33.3%) and Fabaceae (14.3%) species. Rarefaction and extrapolation curves applied for the whole steppe vegetation showed that the expected species richness was stable and no rare species could be found when increasing the sample size. Generalized linear models showed that the variation of plant diversity parameters (alpha-biodiversity) was significant among the phytoecological groups individualized. The multiple factor analysis demonstrated that inter-relationships between the phytoecological groups result from characteristics of soil surface, vegetation indicators, and dominant plant species that influenced plant diversity indices. The qualitative and quantitative analysis of similarity (beta-biodiversity) revealed high resemblances (>50%) between these groups, indicating a spatial homogenization of plant communities, which are dominated by annual species. The variation of phylogenetic diversity, estimated using taxonomic structures (i.e. genus/species and family/species ratios) was related to local environmental conditions. Phylogenetic diversity increased with the increase in total vegetation cover and the average height of Halfa grass (Stipa tenacissima), but it was negatively correlated with land degradation indicators such as sand deposit sheets, bedrock outcrop, coarse-grained materials, and plant necromass or vegetation litter). This study demonstrated that despite the recorded plant diversity, the quality of rangelands in the study area was of a therophytic character (substantial level of annuals), indicating a state of land and vegetation degradation in rangelands of northeastern Algeria.